Leadership for professional learning towards educational equity: a systematic literature review. Issue 4 (7th August 2020) - Poekert, Philip E.; Swaffield, Sue; Demir, Ema K.; A. Wright, Sage
ABSTRACT: This systematic review of recent research explored the uncharted intersection of literature on educational leadership, professional learning, and educational equity. It investigated leadership approaches to shaping the professional development and ongoing learning of educators which supports more equitable outcomes for students. The underlying motivation for the work is our concern for the educational experiences and achievements of marginalised students, and for professional learning to address these inequalities. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement, and iterative selection of literature based on relevance and quality judged by the weight of evidence assessments, we identified 41 empirical items for detailed analysis. The outcome was five themes: Critical framing of social justice issues; Dialogue and enquiry; Learning and identity development; Context, resources, and motivations; Normalising inclusion and shared leadership. A further six articles informed a conceptual framework linking professional learning and outcomes that developed existing models. Critique of linear conceptualisations of learning, and affinity with the values and philosophy of the process model of education championed by Lawrence Stenhouse, prompted proposing the themes as nascent principles. These require further research, yet they have immediate practical utility for educational leaders and teachers working in pursuit of educational equity.